"Chemical Blowing" of Sausage‐Like Carbon Nanotubes with Oriented Graphene‐Layer Walls. Issue 9 (3rd August 2016) - Zhong, Bo; Liu, Defei; Yu, Yuanlie
Abstract: Sausage‐like carbon nanotubes (SLCNTs) have been fabricated via a facile thermal treatment of a homogeneous solution of ammonia borane/dimethylethanolamine with anodic alumina oxide as a template in the absence of metal catalysts. The walls of these SLCNTs contain layers of graphene oriented at an angle towards the tube axis, deviating from the general structure of multi‐walled carbon nanotubes in which all lattice walls are parallel along the longitudinal axis. The current versus voltage measurements perpendicular to the axis reveals that the SLCNTs possess a resistivity of ∼80 Ω m. Abstract : Sausage‐like carbon nanotubes with walls made of graphene layers oriented at an angle to the tube axis are fabricated via a facile thermal treatment of a homogeneous solution of ammonia borane/dimethylethanolamine with anodic alumina oxide as a template in the absence of metal catalysts.